2011
DOI: 10.1093/jxb/err014
|View full text |Cite
|
Sign up to set email alerts
|

The final split: the regulation of anther dehiscence

Abstract: Controlling male fertility is an important goal for plant reproduction and selective breeding. Hybrid vigour results in superior growth rates and increased yields of hybrids compared with inbred lines; however, hybrid generation is costly and time consuming. A better understanding of anther development and pollen release will provide effective mechanisms for the control of male fertility and for hybrid generation. Male sterility is associated not only with the lack of viable pollen, but also with the failure o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
236
0
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(254 citation statements)
references
References 135 publications
4
236
0
7
Order By: Relevance
“…After enzymatic lysis of the septum, and the likely induction of programmed cell death, the septum ruptures to form a single locule and is followed by subsequent opening of the anther. 26 Although septum breakdown is absent in Ginkgo, the sporangium opens on the facing sides of two adjacent microsporangia, 25 which is similar to anther opening in angiosperms. However, in M. glyptostroboides, each microsporangium opens directly and independently along the dehiscence line.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…After enzymatic lysis of the septum, and the likely induction of programmed cell death, the septum ruptures to form a single locule and is followed by subsequent opening of the anther. 26 Although septum breakdown is absent in Ginkgo, the sporangium opens on the facing sides of two adjacent microsporangia, 25 which is similar to anther opening in angiosperms. However, in M. glyptostroboides, each microsporangium opens directly and independently along the dehiscence line.…”
Section: Discussionmentioning
confidence: 97%
“…25 In contrast, anther dehiscence in angiosperms has been studied extensively on a number of species, such as Arabidopsis, Lilium, rice, maize and members of the Solanaceae. 26 The basic processes of anther dehiscence in angiosperms are similar and involve secondary thickening in the anther endothecium, breakdown of the septum, splitting of the stomium and subsequent opening of the anther. 26 Results from the present study show that, during the development of the microsporangial wall and the process of microsporangium dehiscence, M. glyptostroboides displays the following two characteristics.…”
Section: Disclosure Of Potential Conflicts Of Interestmentioning
confidence: 99%
“…This appears to be the major cause of the observed reduction in fertility. The maturation of stamens involves cell elongation of the stamen filament, which synchronizes with development of the other floral organs to maximize the fertilization efficiency (Scott et al, 2004;Wilson et al, 2011). It is possible that AP-2 plays a role in filament cell elongation that requires cell wall biogenesis.…”
Section: Ap-2 Plays Roles In Floral Organ Developmentmentioning
confidence: 99%
“…Mutations of genes involved in the biosynthesis and signaling of these phytohormones affect stamen filament elongation, anther dehiscence, and pollen viability. However, the molecular mechanisms underlying these effects are unknown (Scott et al, 2004;Wilson et al, 2011). AP-2 may play a role in clathrin-mediated endocytosis for the regulation of phytohormone signaling during floral organ development.…”
Section: Ap-2 Plays Roles In Floral Organ Developmentmentioning
confidence: 99%
“…This region subsequently defines the position of anther opening and does not develop the secondary thickening seen in the endothecium and connective tissues. Dehiscence is a two-phase process involving initial enzymatic degradation of the septum separating the two locules, followed by retraction of the locules resulting in a split at the stomium (Wilson et al, 2011). By a combination of molecular genetic analysis and mathematical modeling, we have shown that the mechanical control of opening is mediated by the bilayer structure of the mature anther wall (Nelson et al, 2012).…”
mentioning
confidence: 99%